The Impact of Agricultural Digitization on Land Productivity: An Empirical Test Based on Micro Panel Data - Hongming Zhang; Haihua Zhu (Land)
Digital technology has transformed agriculture by changing traditional production methods and resource allocation. This paper investigates how agricultural digitization affects land productivity, based on farm household data. Findings indicate that agricultural digitization significantly enhances land productivity, with results remaining robust under sensitivity and endogeneity tests. Heterogeneity analysis reveals that the positive effects are more pronounced for larger landholdings, lower levels of human capital, and older farming populations. Mechanism analysis indicates that agricultural digitization improves land productivity by optimizing resource allocation, reducing pollution, enhancing risk resilience, and facilitating the adoption of new technologies. These findings provide valuable insights for developing countries pursuing agricultural digital transformation.